The Role of Job Characteristics, Empowerment and Promotion for Job Satisfaction - Siti Djamilah; Surenggono Surenggono (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
Job satisfaction is important because it can form an atmosphere of togetherness, a healthy organizational climate and high morale. Thus the goals of an organization can be achieved. To create job satisfaction, it is necessary to design a job using a job characteristics model called the job characteristics theory. In addition, empowerment and promotion are needed. This study aimed to examine the effect of job characteristics, empowerment, and promotion on job satisfaction. The sample of this research is students who are already working, employees and lecturers of the Faculty of Economics and Business, Universitas Wijaya Kusuma Surabaya, with the following criteria: at least they have worked in the same place for two years. The sample size is 109 people. The analysis technique used is multiple linear regression. Before testing the hypothesis, the validity and reliability tests are first carried out. The results of the validity and reliability test show valid and reliable results. The results of hypothesis testing indicate that job characteristics and job promotions have a significant effect on job satisfaction, while empowerment has no significant effect on job satisfaction. Therefore, companies/agencies need to improve job characteristics through intensive and varied training so that employee skills vary and provide fair and open promotions. To increase empowerment, it is necessary to give responsibility and authority to workers to make decisions. The results of the validity and reliability test show valid and reliable results.